Handbook of safeguarding global financial stability political, social, cultural, and economic theories and models - Caprio, Gerard; Bacchetta, Philippe; Barth, James R.; Hoshi, Takeo; Lane, Philip R. 1969-; Mayes, David G.; Mian, Atif 1975-; Taylor, Michael 1962- (Academic Press, 2013)
Political and social forces exert pressure on our globalized economy in many forms, from formal and informal policies to financial theories and technical models. Our efforts to shape and direct these forces to preserve financial stability reveal much about the ways we perceive the financial economy. The Handbook of Safeguarding Global Financial Stability examines our political economy, particularly the ways in which these forces inhabit our institutions, strategies, and tactics. As economies expand and contract, these forces also determine the ways we supervise and regulate. This high-level examination of the global political economy includes articles about specific countries, crises, and international systems as well as broad articles about major concepts and trends. Substantial articles by top scholars sets this volume apart from other information sources. Diverse international perspectives result in new opportunities for analysis and research. Rapidly developing subjects will interest readers well into the future.